MANAGEMENT OF FUSARIUM WILT OF TOMATO BY WEEDS AND MYCOFLORA PROCESSED WEEDS COMPOST - VIBHA; NIDHI (The Bioscan, 2014)
The plant disease suppressing ability of weed along with biocontrol agents has not been adequately evaluated, despite of its proven allelopathic and nutritional values. In the present study; seven weeds extracts, fungus loaded weed compost’s extracts and weed composts pre-decomposed by beneficial fungi were tested against Fusarium wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici (FOL). Although, the weed extracts had inhibitory effect on mycelia growth of Trichoderma virens that ranged between 5.3-34.3 mm, but to lower extent of 16.046.7 mm on Trichoderma harzianum. However, contrast results were obtained in case of Aspergillus niger (2141 mm) and Cladosporium cladosporioides (22.7-32.0 mm), in plate inhibition trial. Almost all the weed extracts, compost extract of Cannabis sativa loaded individually with T. virens (22.33 mm), T. harzianum (22 mm), A. niger (23.83 mm) and C. cladosporioides(21.83 mm) exerted significant inhibitory effect on the growth of the test pathogen (FOL), under in vitro conditions. In pot experiments, Parthenium hysterophorus compost predecomposed individually by T. harzianum and A. niger had significantly reduced the wilt incidence to 20.02% and 18.34% respectively, in tomato crop. Similarly, Physalis minima compost prepared from inoculation of P. lilacinus was significantly identical to former composts in suppressing the wilt incidence (23.34 %) caused by Fusarium oxysporum f.sp. lycopersici. Our results indicate that the disease suppressive effect of weed compost combined with potential bioagents seems to be effective against Fusarium wilt of tomato, due to combined effect of the use of nutrient rich weed composts that support biocontrol agent’s activity without stimulating the activity of pathogens.